Food and energy security - Association of Applied Biologists (Wiley & Sons and the Association of Applied Biologists, 2012)
Food and Energy Security seeks to publish high quality and high impact original research on agricultural crop and forest productivity to improve food and energy security.
Keywords: Climatic changes : Periodicals; Crop improvement : Periodicals; Food security : Periodicals; Energy security : Periodicals; Biology : Periodicals; Biology; Climatic changes; Crop improvement; Energy security; Food security; Agriculture - General